2017
DOI: 10.4103/njcp.njcp_108_16
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients and oncology nursing: Perspectives of oncology nurses in Turkey

Abstract: According to the findings of this study, nurses declared that working with cancer patients increase burnout, they are insufficient in managing work stress and giving psychological care to patients, but their job satisfaction, clinical skills and awareness regarding priorities of life has increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
2
15
0
4
Order By: Relevance
“…Furthermore, rewarding feedback from the patients was another positive aspect for the HCP. These findings are consistent with a study from Kamisli et al 20 among Turkish oncology nurses, in which nurses indeed expressed their exhaustion but also their increased levels of empathy, patience, awareness about priorities in life and job satisfaction. Despite an excessive workload, Australian oncology nurses showed high levels of personal satisfaction and personal accomplishments in a survey among 234 nurses.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, rewarding feedback from the patients was another positive aspect for the HCP. These findings are consistent with a study from Kamisli et al 20 among Turkish oncology nurses, in which nurses indeed expressed their exhaustion but also their increased levels of empathy, patience, awareness about priorities in life and job satisfaction. Despite an excessive workload, Australian oncology nurses showed high levels of personal satisfaction and personal accomplishments in a survey among 234 nurses.…”
Section: Discussionsupporting
confidence: 92%
“…It can be assumed that this results from heavy workload. Nurses report that their work is emotionally tiring and low-paid (Fuente-Solana et al 2017;Kamisli et al 2017;Mcmillan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kamisli et al ., providing training and psychological support, gaining awareness of individual limitations, exercising, and physical activities to better deal with the problems of oncology nursing have been suggested. [ 10 ] Moreover, the results of a study showed that designing self-care programs and training oncology nurses in this field is required to promote their health. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that the most required skills for oncology nurses were patience, empathy, and work experience. [ 10 ] Participants of the present study believed that specialized training was needed for oncology nursing. The results of studies in Iran, Turkey, and Nigeria also showed that oncology nurses should specifically be trained through specialized cancer nursing education courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation